(untitled) (Analele Universității București. Limba și literatură română, 2024)
The object of my analysis is the fantastic character of the Flying Incubus, known in the Romanian folklore as the Sburător [The Flyer], reinterpreted by three Romantic poets, I. Heliade Rădulescu, Cezar Bolliac, and V. Alecsandri. In their poems that share the same title, Sburătorul, they associate different values to this character, commonly seen as a seducer of young girls, appearing to them at night and consuming them with a strange passion that can lead to the girls’ death: for Heliade Rădulescu, the Flying Incubus is very similar to a vampire, Alecsandri depicts him as a sort of fawn, whereas in Bolliac’s poem he is an erotic demon. This character’s recurrence in Romanian 19th century literature is an influence of the Romanticism from two points of view: the discovery of the folklore as a source of poetic inspiration and the attraction for dark love, as analyzed by Mario Praz.